2022
DOI: 10.1155/2022/2466006
|View full text |Cite
|
Sign up to set email alerts
|

The Systematic Analyses of RING Finger Gene Signature for Predicting the Prognosis of Patients with Hepatocellular Carcinoma

Abstract: RING finger (RNF) proteins are frequently dysregulated in human malignancies and are tightly associated with tumorigenesis. However, the expression profiles of RNF genes in hepatocellular carcinoma (HCC) and their relations with prognosis remain undetermined. Here, we aimed at constructing a prognostic model according to RNF genes for forecasting the outcomes of HCC patients using the data from The Cancer Genome Atlas (TCGA) program. We collected HCC datasets to validate the values of our model in predicting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…MKLN1-AS affects HCC progression by regulating microRNAs ( 62 ). Several studies have also reported that AL031985.3, TMCC1-AS1, LINC01224, SNHG10, RNF216P1, and AC025176.1 are potential prognostic predictors in HCC ( 63 - 69 ). AL031985.3, an immune- and autophagy-related lncRNA, was shown to be a predictor for HCC prognosis ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…MKLN1-AS affects HCC progression by regulating microRNAs ( 62 ). Several studies have also reported that AL031985.3, TMCC1-AS1, LINC01224, SNHG10, RNF216P1, and AC025176.1 are potential prognostic predictors in HCC ( 63 - 69 ). AL031985.3, an immune- and autophagy-related lncRNA, was shown to be a predictor for HCC prognosis ( 63 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms within RNF145's coding region in humans are associated with obesity and dyslipidemia while its differential expression in hepatocellular carcinoma affects disease progression. [74][75][76][77] RNF145's lipid-modulating effects are intimately linked to its ability to target lipid metabolic enzymes for degradation. [74,[78][79][80][81] Accordingly, RNF145's substrates include the ER-resident lipid hydrolase adiponectin receptor 2 (ADIPOR2) and the cholesterol biosynthetic enzyme HMGCR.…”
Section: Rnf145mentioning
confidence: 99%
“…Single nucleotide polymorphisms within RNF145's coding region in humans are associated with obesity and dyslipidemia while its differential expression in hepatocellular carcinoma affects disease progression. [ 74–77 ]…”
Section: Introductionmentioning
confidence: 99%
“…The cost-efficiency of using biomarkers to screen patients at risk of developing HCC is a topic of debate [ 10 , 11 ]. Multiple biomarkers have been studied for their potential role in the surveillance and early detection of HCC, alongside new prognostic or therapeutic targets for HCC [ 12 , 13 ]. Among them, alpha-fetoprotein (AFP) is the most extensively studied, and guidelines recommend it be used with ultrasound to screen patients at risk for HCC [ 6 ].…”
Section: Introductionmentioning
confidence: 99%